Preparation method and filling method of calcium aluminate self-leveling pouring hole sealing material
By adopting the preparation method of calcium aluminate self-leveling casting pore sealing material and its filling method, the problem of tin liquid penetrate into the brick joints is solved, and the effective sealing of tin liquid and the improvement of glass quality is achieved.
Patent Information
- Application Number
- CN202411957208.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-04-29
AI Technical Summary
In the production of float glass, temperature fluctuations in the tin tank cause tin liquid to penetrate into the brick joints, causing bubbles in the tank body and affecting the quality of the glass. The existing sealing material does not match the performance of the bottom brick, and improper construction leads to leakage of tin liquid.
The preparation method of calcium aluminate self-leveling cast pore sealing material and its filling method are adopted. Through the specific raw material composition and process flow, a pore sealing material is prepared with high pressure resistance and good tin liquid permeability resistance, and the optimal filling method is used to ensure the good combination of the pore sealing material and the tin slot holes.
It realizes effective sealing of tin liquid, prevents tin liquid from penetrateing into the brick holes, reduces the occurrence of bubbles in the tank body, and improves the quality of glass.
Smart Images

Figure CN119898950A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a preparation method of a calcium aluminate self-leveling pouring sealing material and a filling method thereof. Background Art
[0002] In the float glass forming process, the batch material is melted, clarified, homogenized and other operations in the melting furnace to form glass liquid, which then enters the tin bath to be flattened and polished to form a flat glass substrate. As a key thermal equipment in the float glass production process, the quality of the tin bath will seriously affect the quality of the glass. The quality of the tin bath is directly related to the material and construction quality of the tin bath bottom bricks, both of which are equally important. The quality of bricks lies in accurate size, no cracks, uniform structure and low permeability. At present, the bottom of the tin bath of the float line generally uses high-quality low-alkali clay bricks; the construction materials should choose matching sealing materials and their appropriate filling solutions.
[0003] However, during production, if the temperature in the tin bath fluctuates, the tin liquid will intrude into the brick joints. The gas in the gap will overflow upward along the brick joints, pass through the tin liquid and reach the bottom of the glass strip floating on the tin liquid surface, forming bubbles in the tank, which will have a serious impact on the quality of the glass. If the material of the sealing material does not meet the design requirements and does not match the performance of the bottom brick material; or the sealing material is improperly constructed, layered and rammed, and the sealing material and the inverted cone hole of the bottom brick are not well combined, it will cause tin liquid leakage. Therefore, it is of great significance to invent a new type of tin tank hole sealing material and its optimized filling method. Summary of the invention
[0004] In view of the problems existing in the background technology, the present invention provides a preparation method of a calcium aluminate self-leveling pouring sealing material and a filling method thereof. The obtained sealing material has high compressive strength and good resistance to tin liquid penetration, and can effectively prevent tin liquid from penetrating into the brick holes. It is achieved by the following technical solutions: In a first aspect, the present invention provides a method for filling a calcium aluminate self-leveling pouring sealing material, comprising the following steps: Step (1): prepare a complete tin bath bottom brick with holes, a stirrer, a pouring fixing ring, a vibrating rod and a cutting machine. First, reinforce the pouring fixing ring close to the top of the tin bath hole. When pouring, the sealing material is flush with the pouring ring. Step (2): During the pouring process, add 3-10% water to find the appropriate pouring capacity through experiments, and then pour it into the bolt holes of the fixed secondary groove bottom bricks; Step (3): After casting, the mold is cured at room temperature for 24 hours, and then placed in an electric furnace for drying and sintering; Step (4): After drying, cut the part higher than the tin bath brick surface with a cutting machine and polish it smooth; Step (5): Inspect the finished product, cut it in the longitudinal and transverse planes to check the bonding state between the sealing material and the hole wall, and observe the bonding state between the sealing material and the tin slot hole after high-temperature sintering.
[0005] In step (1), the diameter of the casting fixing ring is 200 mm and the height is 50 mm.
[0006] In step (1), various tin bath bottom bricks are used for comparative casting, and the tin bath bottom bricks include conventional tin bath bottom bricks, low thermal conductivity tin bath bottom bricks, isostatically pressed low thermal conductivity tin bath bottom bricks, and isostatically pressed calcium aluminate tin bath bottom bricks.
[0007] In order to facilitate observation of the fit between the poured material and the brick during pouring in step (2), no heat-resistant steel bolts are added to the bolt holes and no graphite powder is filled in the bottom protection holes.
[0008] In step (3), the electric furnace drying and sintering conditions are calcining at 1100-1250° C. for 18-24 hours.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned calcium aluminate self-leveling pouring sealing material, comprising the following steps: Step (a): weigh calcium aluminate particles and powder, aluminum oxide powder, zirconium silicate powder and zirconium corundum powder according to the number of parts, pour them into a strong mixer, and dry mix for 10 to 15 minutes; Step (b): After the raw materials in step (a) are completely mixed, pure calcium aluminate cement, sintering promoter and water reducing agent are added, and the mixture is stirred for 15 to 30 minutes to obtain a calcium aluminate self-leveling sealing material.
[0010] The raw material portions are: 50-65 parts of calcium aluminate aggregate particles, 10-15 parts of zirconium silicate powder, 8-13 parts of pure calcium aluminate cement, 5-10 parts of calcium aluminate powder, 5-10 parts of alumina powder, 1-5 parts of sintering promoter, 1-5 parts of water reducer, and 10-15 parts of water.
[0011] The sintering promoting agent is selected from one or more of borax, boric acid, calcium silicate or borate.
[0012] The water reducing agent is selected from one or more of lignin, polycarboxylic acid or sulfonate.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The filling method of the present invention is simple to operate and convenient for construction. The raw material components are 51 parts of calcium acid aggregate particles, 12 parts of zirconium silicate powder, 9 parts of pure calcium aluminate cement, 6 parts of calcium aluminate powder, 6 parts of alumina powder, 2 parts of borax, 2 parts of lignin, and 12 parts of water. The prepared castable has good performance. The castable is cast with different tin bath bottom bricks. After observing the bonding state with the tin bath hole after casting, it can be seen that the sealing material is seamlessly bonded with conventional tin bath bottom bricks, low thermal conductivity tin bath bottom bricks, isostatically pressed low thermal conductivity tin bath bottom bricks, and isostatically pressed calcium aluminate tin bath bottom bricks, which can achieve the purpose of slot hole sealing. The porosity is between 20.4% and 21.6%, and the volume density is between 2.63 and 2.72 g / cm 3 The compressive strength is between 105 and 110 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Schematic diagram of the pouring method of tin bath bottom bricks. DETAILED DESCRIPTION
[0015] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0016] It should be noted that the experimental methods used in the implementation examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0017] In the present invention, unless otherwise specified, all "parts" and percentages (%) refer to percentages by weight.
[0018] In the present invention, unless otherwise specified, the sum of all percentages in all compositions is 100%.
[0019] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a-b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0020] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0021] In the present invention, unless otherwise specified, all the steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially; for example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially; for example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0022] In the present invention, unless otherwise specified, the specific numerical values and specific substances in the embodiments of the present invention may be combined with other features of the description part of the present invention; for example, if the specification mentions that the reaction temperature is 10~100°C, and the embodiment mentions that the reaction temperature is 20°C, then it can be considered that the present invention has specifically disclosed the range of 10~20°C, or the range of 20~100°C, and this range can be combined with other features of the description part to form a new technical solution. Example
[0023] Weigh calcium aluminate particles and powder, alumina powder, zirconium silicate powder and zirconium corundum powder according to the number of parts in Table 1, pour them into a strong mixer, and dry mix for 10 to 15 minutes; After the raw materials in the above steps are completely mixed, pure calcium aluminate cement, sintering promoter and water reducer are added, and the mixture is stirred for 15 to 30 minutes to obtain calcium aluminate self-leveling sealing material, and different tin bath bottom bricks are used for comparative casting.
[0024] Prepare a complete tin bath bottom brick with holes, a stirrer, a pouring fixing ring with a diameter of 200mm and a height of 50mm, a vibrating rod and a cutting machine. First, reinforce the pouring fixing ring close to the top of the tin bath hole, pour slowly, add 3-10% water during the pouring process, and experiment to find the appropriate pouring capacity, and inject it into the bolt hole of the fixed secondary bath bottom brick; after pouring, the sealing material should be flush with the pouring ring; After casting, it is cured at room temperature for 24 hours, then placed in an electric furnace for calcination at 1100-1250℃ for 18-24 hours for drying and sintering; After drying, cut the part higher than the tin bath brick surface with a cutting machine and grind it smooth; Inspect the finished product, cut it longitudinally and transversely to check the bonding state between the sealing material and the hole wall, and observe the bonding state with the tin slot hole after high-temperature sintering.
[0025] Table 1 Calcium aluminate aggregate particles / parts Zirconium silicate powder / parts Pure calcium aluminate cement / parts Calcium aluminate powder / parts Alumina powder / parts Sintering agent / parts Water reducing agent / parts Water / parts Tin bath bottom brick Example 1 51 12 9 6 6 Borax 2 Lignin 2 12 Conventional tin bath bottom brick Example 2 51 12 9 6 6 Borax 2 Lignin 2 12 Low thermal conductivity tin bath bottom brick Example 3 51 12 9 6 6 Borax 2 Lignin 2 12 Isostatic Pressing Low Thermal Conductivity Tin Bath Bottom Brick Example 4 51 12 9 6 6 Borax 2 Lignin 2 12 Isostatically pressed calcium aluminate tin bath bottom brick Example 5 55 10 8 5 5 Borax 3 Lignin 2 12 Isostatically pressed calcium aluminate tin bath bottom brick Example 6 50 14 10 6 5 Borax 2 Lignin 2 11 Conventional tin bath bottom brick Example 7 50 10 13 5 7 Borax 1 Lignin 1 13 Conventional tin bath bottom brick Example 8 50 10 13 5 7 Boric acid 1 Lignin 1 13 Conventional tin bath bottom brick Example 9 51 12 9 6 6 Calcium silicate 2 Lignin 2 12 Conventional tin bath bottom brick Example 10 54 12 9 5 6 Calcium silicate 1 Polycarboxylic acid 3 10 Conventional tin bath bottom brick Embodiment 11 50 11 12 8 7 Borate 1 Polycarboxylic acid 1 10 Conventional tin bath bottom brick The raw material composition and product obtained in the embodiment were subjected to performance tests, and the test results are shown in Table 2.
[0026] Table 2 Porosity% <![CDATA[Bulk density g / cm 3 > Compressive strength MPa Firing line change% The degree of bonding between sealing material and brick Example 1 20.6 2.72 110 0.10 Seamless Example 2 21.3 2.63 109 0.07 Seamless Example 3 21.6 2.67 106 0.11 Seamless Example 4 20.4 2.63 105 0.09 Seamless Example 5 26.9 2.57 107 0.04 Loosely bonded, with more pores Example 6 21.9 2.51 99 0.09 Seamless Example 7 21.7 2.48 101 0.11 Seamless Example 8 20.5 2.60 104 0.06 Seamless Example 9 21.9 2.59 108 0.07 Seamless Example 10 22.1 2.65 101 0.13 Seamless Embodiment 11 20.5 2.43 106 0.07 Loosely combined Combining Table 1 and Table 2, it can be seen that the raw material portions of the casting materials in Examples 1 to 4 are the same, and when poured into different tin bath bottom bricks, it is found that the sealing material is seamlessly combined with conventional tin bath bottom bricks, low thermal conductivity tin bath bottom bricks, isostatically pressed low thermal conductivity tin bath bottom bricks, and isostatically pressed calcium aluminate tin bath bottom bricks, which can achieve the purpose of slot sealing, and the sealing material obtained by using the raw material portion has a porosity of between 20.4% and 21.6%, and a compressive strength of 105 to 110 MPa. When Example 5 increases the portion of calcium aluminate aggregate particles to obtain a product, the porosity is 26.9%, and at the same time, it is loosely combined with the tin bath bottom bricks, and there are too many bubbles. The main reason is that the proportion of aggregate particles is too large, which hinders the fluidity of the material and causes the pores to be difficult to discharge. When the proportion of calcium aluminate aggregate is reduced to obtain Examples 6 to 8, the porosity is between 20.5% and 21.9%, and the porosity is significantly reduced. In Example 11, the product obtained by reducing the amount of sintering agent and water reducing agent at the same time is loosely bonded to the tin bath bottom brick. The main reason is that the sealing material obtained by lacking sintering agent and water reducing agent has poor fluidity and low molding strength.
[0027] In summary, the castable with the best performance is obtained by combining 51 parts of calcium aluminate aggregate particles, 12 parts of zirconium silicate powder, 9 parts of pure calcium aluminate cement, 6 parts of calcium aluminate powder, 6 parts of alumina powder, 2 parts of borax, 2 parts of lignin, and 12 parts of water.
[0028] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A filling method of calcium aluminate self-leveling pouring sealing material, characterized in that: The following steps are involved: Step (1): prepare a complete tin bath bottom brick with holes, a stirrer, a pouring fixing ring, a vibrating rod and a cutting machine, first reinforce the pouring fixing ring close to the top of the tin bath hole, and during pouring, the sealing material is flush with the pouring ring; Step (2): during the pouring process, add 3-10% water to find the appropriate pouring capacity through experiments, and inject it into the bolt holes of the fixed secondary groove bottom bricks; Step (3): After casting, curing at room temperature for 24 hours, and then drying and sintering in an electric furnace; Step (4): After drying, cut the bricks by using a cutting machine to remove the part that is higher than the surface of the tin bath bricks, and grind them smooth; Step (5): Inspect the finished product, cut it in the longitudinal and transverse planes to check the bonding state between the sealing material and the hole wall, and observe the bonding state between the sealing material and the tin slot hole after high-temperature sintering.
2. The filling method of the calcium aluminate self-leveling pouring sealing material according to claim 1, characterized in that: The diameter of the casting fixing ring in step (1) is 200 mm and the height is 50 mm.
3. The filling method of the calcium aluminate self-leveling pouring sealing material according to claim 1, characterized in that: The step (1) uses a variety of tin bath bottom bricks for comparative casting, and the tin bath bottom bricks include conventional tin bath bottom bricks, low thermal conductivity tin bath bottom bricks, isostatically pressed low thermal conductivity tin bath bottom bricks, and isostatically pressed calcium aluminate tin bath bottom bricks.
4. The filling method of the calcium aluminate self-leveling pouring sealing material according to claim 1, characterized in that: In order to facilitate observation of the fit between the poured material and the brick during pouring in step (2), heat-resistant steel bolts are not added to the bolt holes and graphite powder is not filled in the bottom protection holes.
5. The filling method of calcium aluminate self-leveling pouring sealing material according to claim 1, characterized in that: The electric furnace drying and sintering conditions in step (3) are calcining at 1100-1250° C. for 18-24 hours.
6. A filling method of calcium aluminate self-leveling pouring sealing material according to claims 1 to 5, characterized in that: The preparation method of the calcium aluminate self-leveling pouring sealing material comprises the following steps: Step (a): weigh calcium aluminate particles and powder, aluminum oxide powder, zirconium silicate powder and zirconium corundum powder according to the number of parts, pour them into a strong mixer, and dry mix them for 10 to 15 minutes; Step (b): After the raw materials in step (a) are completely mixed, pure calcium aluminate cement, sintering promoter and water reducing agent are added, and the mixture is stirred for 15 to 30 minutes to obtain a calcium aluminate self-leveling sealing material.
7. The method for preparing the sealing material in the filling method of calcium aluminate self-leveling casting sealing material according to claim 6, characterized in that: The raw materials are as follows: 50-65 parts of calcium aluminate aggregate particles, 10-15 parts of zirconium silicate powder, 8-13 parts of pure calcium aluminate cement, 5-10 parts of calcium aluminate powder, 5-10 parts of alumina powder, 1-5 parts of sintering promoter, 1-5 parts of water reducer and 10-15 parts of water.
8. The method for preparing the sealing material in the filling method of calcium aluminate self-leveling pouring sealing material according to claim 6, characterized in that: The sintering promoting agent is selected from one or more of borax, boric acid, calcium silicate or borate.
9. The method for preparing the sealing material in the filling method of calcium aluminate self-leveling pouring sealing material according to claim 6, characterized in that: The water reducing agent is selected from one or more of lignin, polycarboxylic acid or sulfonate.